KAJIAN KONSENTRASI SITOKININ DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL BULBIL TANAMAN PORANG (Amorphophallus onchophyllus) - Ramdan Hidayat; Felicitas Deru Dewanti; Guniarti Guniarti (Plumula : Berkala Ilmiah Agroteknologi, 2019)
Porang plants ( Amorphophallus onchophyllus ) is a shrub ( herb ) that the leaves grow armpit bulbil as a breeding tool. In addition to using bulbil porang can also reproduce by using bulbs and seeds. Bulbs to be harvest as result because it has glucomanan compounds that high economic value. Currently there porang tuber production sold to employers to be exported abroad in the form of chips filled with a gathering of farmers iles - iles that grows wild in the environment and forestry plantations. Intensive cultivation efforts should be supported by the availability of seedlings. Therefore, it needs to be study with seedlings originating from sources other than the tubers, ie with bulbil. The purpose of the study is 1) Knowing the effect of combined treatment of sitokinin (CPPU) concentration and dose of NPK fertilizer on growth and yield porang 2) Knowing sitokinin (CPPU) concentration effective in improving plant growth of porang and 3) Knowing the optimum dose of NPK fertilizer on plant growth porang. This experiment is a factorial experiment with 2 (two) factors which are arranged in a completely randomized design (CRD) and repeated 4 times. The first factor is the concentration CPPU (K), which consists of : K0 = Without CPPU (control), CPPU 5 ppm = K1, K2 = CPPU 10 ppm, 15 ppm CPPU = K3 and K4 = CPPU 20 ppm. While the second factor is the dose of fertilizer N , P and K (P) consisting of : P1 = dose of NPK fertilizers (Urea 15 g, SP36 7.5 g, KCl 7.5 g), P2 = dose of NPK fertilizers (Urea 20 g , SP36 10 g, 10 g KCl) and P3 = dose of NPK fertilizers (Urea 25 g, SP36 12.5 g, 12.5 g KCl). Observations were made on growth and development, as well as crop yields porang, which consists of: plant height (cm), leaf canopy width (cm), stem diameter (cm), number of bulbil, bulb diameter (cm) and weight of tubers per plant. The results showed that: 1) There was no significant interaction of all variables observation, 2) Concentration CPPU very significant effect on canopy leaf width and number of bulbil. Concentration CPPU 20 ppm produces a wide canopy of leaves and number of bulbil highest with increased width of the leaf canopy by 38 % and increase in number of bulbil by 87% compared with controls. 3) Fertilizer doses very significant effect on canopy leaf width and number of bulbil. Dose of NPK fertilizer 25 g urea, 12.5 g SP36 and 12.5 g KCL (P3), shows the results of the leaf canopy width and number of bulbil highest with increased width of the leaf canopy by 34% and increase of number bulbil by 67% compared with fertilizer treatment 15 g of urea, 7.5 g SP-36 and 7.5 g KCL (P1).